Foreign ownership, capital structure, and dividend policy affect on firm value in IDX cement companies - Fadil, Mohammad; Kadang, Juliana (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
This study aims to determine how foreign ownership, capital structure and dividend policy affect on the firm value in cement companies listed on the IDX. This type of research is a quantitative approach and uses descriptive method techniques to describe existing phenomena. In this study, the sample was determined as many as 6 companies, the companies are cement companies listed on the IDX. The results of the study using panel data regression analysis tools showed that foreign ownership has a positive but insignificant effect on the firm value in cement companies listed on the IDX. Capital Structure has a positive but insignificant effect on the firm value in cement companies listed on the IDX. Dividend policy has a positive and significant effect on the firm value in cement companies listed on the IDX. Foreign ownership, Capital structure and dividend policy simultaneously have a positive and significant effect on the firm value in cement companies listed on the IDX.